Determinacija spola i morfološke osobine sivog puha (Glis glis) s područja Dalmatinske zagore Determination of sex and morphological characteristics of fat dormouse (Glis glis) from the area of Dalmatian hinterland - Pervan, Ivan, agronom; Radočaj, Tena; Tomljanović, Tea; Bujanić, Miljenko; Konjević, Dean (2019)
Sivi puh (Glis glis L.) je najveći pripadnik porodice puhova. Arborealna je i nokturnalna životinja koja je autohtona vrsta divljači u Hrvatskoj. U radu su obrađeni morfološki parametri, kao što su mase (tijelo s repom, tijelo bez repa, glava, rep, jetra, bubreg, srce, pluća, puno probavilo i radman) i duljine pojedinih dijelova tijela (tijelo s repom, tijelo bez repa, rep te raspon prednjih i stražnjih udova), izmjereni na 32 adultne jedinke (18 ženki i 14 mužjaka) ulovljenim tijekom lovne sezone 2017./2018.) na području Dalmatinske zagore. Statistički značajna razlika između mužjaka i ženki utvrđena je u duljini tijela bez repa (p=0,049) i masi repa (p= 0,041), mužjaci imaju veće vrijednosti za obje značajke. Ostali izmjereni parametri nisu pokazali statitistički značajnu razliku između spolova. Spolni dimorfizam kod ovog glodavca nije izražen, iako mužjaci u prosjeku imaju nešto veću masu od ženki. Na temelju boje krzna i veličine tijela nije moguće razlikovati adultne od juvenilnih jedinki. Izmjereni morfološki parametri uglavnom se podudaraju s rezultatima sličnih istraživanja.
Edible dormouse (Glis glis L.) is the largest dormouse species. The edible dormouse is autochthonous game species in Croatia, and arboreal animal that is active at night. During the hunting season 2017./2018. we have collected 32 adult individuals (18 females and 14 males), on the area Dalmatian hinterland. Following sex determination, the following morphological parameters were measured: mass (total mass including tail, total mass without tail , head, tail, liver, kidney, heart, lung, digestive system and radman) and body length measurements (body length including tail, body length without tail, front and back width of the puck and tail length). Statistically significant difference between males and females was found in the length of the body without the tail (p = 0.049) and tail mass (p = 0.041), with males displaying greater values for both of these features. The other measured parameters did not show significant differences between sexes. Sexual dimorphism in this rodent is not pronounced, though on average males tend to be larger and heavier than females. It was not possible to differentiate adults and juveniles based on the color of the fur and the body size. Measured morphological parameters mostly coincide with results of similar research. Edible part of internal organs constitutes 5.1% of live weight (heart and lungs 1.8%, livers 2.43% and kidneys 0.8%). Non-edible part includes stomach and intestines (12.3%), head (11.78%), tail (4%) and skin and metapodia (11.21%). Sex of an individual Edible dormouse can be safely determined by looking at the external sex organs. Body length and total mass of Edible dormouse in Dalmatian hinterland is similar to the population in the Gorski Kotar region.
Bibliografija: str. 575-576.
Sažetak ; Summary.
Keywords: Sivi puh -- Glis glis -- Morfološke osobine -- Spolni dimorfizam; Dalmatinska zagora